In Silico Evaluation of Inhibitory Potential of Sulfonamide Derivatives against Diadenosine Tetraphosphate Hydrolase as Antimalarial Agents - Bhati, Shipra (Asian Journal of Pharmaceutics (AJP), 2017)
Aims: Malaria remains a worldwide health problem. Resistance to antimalarial drugs by the Plasmodium falciparum malaria parasite is posing a serious impediment in malaria control program. Hence continuous efforts on the development of new antimalarial are required. Being an important enzyme in parasite physiology diadenosine tetraphosphate (Ap4A) hydrolase may prove a good target for antimalarial drugs. The aim of this study was to explore the inhibitory potential of some sulfonamide derivatives against malaria parasite Ap4A hydrolase. Materials and Methods: The molecular three-dimensional structural data of malaria parasite Ap4A hydrolase were obtained from protein databank (PDB ID: 5CFI) and used as a drug target. The molecular docking approach was employed to find out the in silico inhibitory potential of the sulfonamide derivatives against Ap4A hydrolase and their relative stabilities were studied. Results and Discussion: All sulfonamide derivatives showed good binding affinity against the target protein. The binding free energy of compound 4-amino-N-(quinoxalin-2yl) benzenesulfonamide S6 (âˆ’8.43 Kcal/mole) showed it to be the most optimal sulfonamide derivative as inhibitor for Ap4A hydrolase enzyme. Conclusions: Evaluation of binding affinities using free energy simulations allowed establishing that sulfonamides having quinoxaline moiety is the highest quality compound of the series. The findings attained through this study on the molecular interaction mode of sulfonamide derivatives, and Ap4A hydrolase enzyme can be considered for further in vitro and in vivo validation for designing new potential antimalarial drugs.